Caprock self-sealing effect due to CO2 leakage from geologic carbon sequestration reservoirs: a case study at Ping’an, China - Fu, Lei; Diao, Yujie; Zheng, Changyuan; Ma, Xin; Zhang, Chenglong; Liu, Ting; Jin, Xiaolin; Shao, Wei (Frontiers in Energy Research, 2022)
As a bottom technology for CO2 reduction, geological CO2 storage has attracted great attention from geologists, but there are few reports on the research of the caprock self-sealing effect due to CO2 leakage. Ping’an is a natural CO2 leakage site, which can be compared to the leakage scenarios of geological CO2 storage. Based on the water quality test results and geological observation data, the numerical simulation of geochemistry is carried out. The results show that: First, gypsum dissolves and calcite precipitates during the migration of CO2-rich water to the surface. This process presents a self-sealing effect, and the closer to the surface, the more obvious the self-sealing; Second, the self-sealing effect is formed rapidly. For a 30 cm wide fissure, it only takes a few hundred days to achieve self-sealing; Third, the CO2 leakage was estimated, about 140,813.3 m3, or about 251.28 tons for 1 m long fissure.